Combination Therapy for Hypothyroidism: Rationale, Therapeutic Goals, and Design - Madan, Ritu; Celi, Francesco S. (Frontiers in Endocrinology, 2020)
Hypothyroidism is a common condition with a wide spectrum of etiologies and clinical manifestations. While the majority of patients affected by hypothyroidism respond well to levothyroxine, some patients do not and complain of symptoms despite adequate replacement. There is evidence in experimental models of hypothyroidism that levothyroxine alone may not be able to deliver adequate amount of T3 to all the tissues target of the hormonal action, while Liothyronine/Levothyroxine combination therapy can. The results of clinical studies directed to assess the effectiveness of Liothyronine/Levothyroxine combination therapy on the amelioration of hypothyroid symptoms have been disappointing. Most of the trials have been short, underpowered, and with several shortcomings in the study design. There is consensus that an adequately powered clinical trial should be developed to prove or disprove the efficacy and effectiveness of non LT4-only therapy for the treatment of hypothyroidism, and to assess which group of patients would benefit from. Here we present some considerations on the technical aspects and necessary tradeoffs in designing such a study with a particular focus on study population selection, choice of endpoints, and study drugs formulation and regimen.